Environmental performance evaluation of suppliers: A hybrid fuzzy multi-criteria decision approach - Tuzkaya, G.; Ozgen, A.; Ozgen, D.; Tuzkaya, U. R. (SPRINGER, 2009)
Increasing environmental problems enforce companies to be more environmental responsible. A company's environmental performance is not only related to the company's inner environmental efforts, but also it is affected by the suppliers' environmental performance and image. As a stakeholder of the company, a supplier with bad environmental image affects badly the company's environmental image. Also, raw materials and semi-finished products supplied from out of the company recourses-suppliers-affects the products environmental features such as life cycle, re-usability, re-manufacturability, hazardous substances, etc. Considering these direct and indirect effects, managers should also consider environmental performances of their suppliers in their supplier evaluation process. In this paper, a methodology for the evaluation of suppliers' environmental performances is proposed. In this methodology, a hybrid Fuzzy-Analytic Network Process and Fuzzy-Preference Ranking Organization METHod for Enrichment Evaluations approach is utilized. Additionally, a numerical example is given to foster the better understanding of the methodology and the obtained results are analyzed with sensitivity analyses.
Keywords: Decision-making; Environmental criteria; Fuzzy sets; Green supply chain; ANALYTIC NETWORK PROCESS; EXTENT ANALYSIS METHOD; PROMETHEE METHOD; SELECTION; AHP; MODEL; CRITERIA; RANKING; DESIGN; MANAGEMENT; Environmental Sciences & Ecology